Survival Outcomes of Patients With Epidermal Growth Factor Receptor Mutations in Non-Small Cell Lung Cancer With Leptomeningeal Metastasis - Li, Ning; Bian, Zhimin; Cong, Minghua; Liu, Yutao (Frontiers in Oncology, 2022)
Background Leptomeningeal metastasis (LM) is a commonly observed complication in patients with epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC). This study aimed to investigate the gene mutations, treatment strategies, and clinical outcomes in patients with LM. Methods We retrospectively analyzed the clinical and survival outcomes of 53 patients with EGFR-mutated NSCLC with LM. Results The median overall survival after LM diagnosis was 13.0 months, ranging from 0.5 to 42.0 months (95% CI = 9.067–16.933), with 64.2% maturity. Patients who received osimertinib after developing LM (n = 35) had a significantly higher rate of LM disease control (p = 0.008) and significantly longer overall survival (15.0 versus 6.0 months; hazard ratio (HR), 2.4292; 95% CI, 1.234–4.779; p = 0.045) than those who received previous generations of EGFR tyrosine kinase inhibitors (TKIs) or other localized therapies (n = 6). Logistic regression analysis showed that LM disease control status was a positive predictive factor for overall survival after developing LM (p < 0.001, odds ratio = 10.797, 95% CI = 4.102–28.419). Conclusions Our study provides real-world clinical evidence that patients with EGFR-mutated NSCLC diagnosed with LM who developed LM had better clinical outcomes with osimertinib therapy. Our findings also suggest that LM disease control is the most effective strategy to prolong the overall survival outcomes of these patients.